No hemoglobin but NO: the icefish (Chionodraco hamatus) heart as a paradigm - Pellegrino, D.; Palmerini, C. A.; Tota, B. (Journal of Experimental Biology, 2004)
The role of nitric oxide (NO) in cardio-vascular homeostasis is now known to include allosteric redox modulation of cell respiration. An interesting animal for the study of this wide-ranging influence of NO is the cold-adapted Antarctic icefish Chionodraco hamatus , which is characterised by evolutionary loss of hemoglobin and multiple cardio-circulatory and subcellular compensations for efficient oxygen delivery. Using an isolated, perfused working heart preparation of C. hamatus , we show that both endogenous (l-arginine) and exogenous (SIN-1 in presence of SOD) NO-donors as well as the guanylate cyclase (GC) donor 8Br-cGMP elicit positive inotropism, while both nitric oxide synthase (NOS) and sGC inhibitors, i.e. l-NIO and ODQ, respectively, induce significant negative inotropic effects. These results therefore demonstrate that under basal working conditions the icefish heart is under the tonic influence of a NO-cGMP-mediated positive inotropism. We also show that the working heart, which has intracardiac NOS (shown by NADPH-diaphorase activity and immunolocalization), can produce and release NO, as measured by nitrite appearance in the cardiac effluent. These results indicate the presence of a functional NOS system in the icefish heart, possibly serving a paracrine/autocrine regulatory role.